Shear capacity of HPFRC beams flexurally reinforced with steel and prestressed GFRP bars - Soltanzadeh, Fatemeh (2013)
This paper presents the relevant results from an experimental program to assess the shear capacity of high performance fiber reinforced concrete (HPFRC) beams flexurally reinforced with a hybrid system of passive steel and prestressed GFRP longitudinal bars. Three series of two beams with different level of prestressing were tested. The effect of prestressing level on the shear capacity of the beams was the main investigated parameter. The results showed an enhancement of the load carrying capacity, ductility and energy absorption with the increase of the prestress level. Based on the obtained results, the predictive performance of the analytical formulations of CEB-FIP Model Code 2010 and RILEM TC 162-TDF for the shear capacity of FRC beams was assessed. Both formulations seem appropriate for design purposes, but the CEB-FIP formulation predicts more conservative shear capacity. The experimental results demonstrated that the prestressing level has an effect on the shear capacity much higher than the one recommended by the codes.